Temporal association between SARS-CoV-2 and new-onset myasthenia gravis: is it causal or coincidental? - Muralidhar Reddy, Y (BMJ Case Rep, 2021)
Several case reports of COVID-19 in patients with myasthenia gravis (MG) have been documented. However, new-onset autoimmune MG following COVID-19 has been reported very rarely. We report one such case here. A 65-year-old man presented to us with dysphagia 6 weeks following mild COVID-19. He was evaluated and diagnosed as antiacetylcholine receptor antibody (AchR) positive, non-thymomatous, generalised MG. He subsequently developed myasthenic crisis and improved after treatment with intravenous immunoglobulin, prednisolone and pyridostigmine. Systematic literature review showed eight more similar cases. Analysis of all cases including the one reported here showed these features: mean age 55.8 years, male gender (5), time interval between COVID-19 and MG (5–56 days), generalised (5), bulbar and/or ocular symptoms (4), anti-AchR antibodies (7) and antimuscle-specific kinase antibodies (2). All have improved with immunotherapy. Although, many hypothesis are proposed to explain causal relationship between the two, it could as well be sheer coincidence.